Analisis Validitas Jobsheet Trainer Langlois Tag-2 sebagai Penunjang Praktek Instalasi Perumahan - Wahyu Wahyu; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research was carried out because the housing installation practice course did not yet have a jobsheet for the operation of the Langlois Tag-2 media trainer, the purpose of this research was to create a jobsheet for the Langlois Tag-2 media trainer whose benefits were to support the learning process of the housing installation course. This study uses the R&D development procedure (research and development) using a 4D model, consisting of the define, design, develop, and desiminate stages. The research data was taken using a questionnaire sheet for the validity of the jobsheet by the validator, namely the lecturer of the housing installation course. The method of data analysis in this research is descriptive quantitative. The results of the study obtained validity data from 3 validators, namely validator 1 is very valid, validator 2 is very valid, and validator 3 is very valid, the results of the three validators can be categorized as very valid with an average result of 87, 10%. With valid development results, the jobsheet can be used as a support for residential installation practice courses by utilizing the Langlois Tag-2 media trainer at the Department of Electrical Engineering, Padang State University.